Enhanced durability of round bamboo treated with copper naphthenate under heat-cold impregnation - Jun Jiang; Shuaibo Han; Xin Ren; Hui Wang; Hongwei Yu; Fangli Sun (Royal Society Open Science, 2022)
Round bamboo has aroused much interest in construction for its mechanical properties, but poor biological durability seriously restricts its application. In order to develop a suitable and effective preservative treatment method for round bamboo, copper naphthenate (CuN) was adopted and impregnated into round bamboo using heat-cold procedure. The distribution and retention of copper naphthenate in round bamboo were studied, and the biological durability represented by the mould and decay resistance were investigated. The results showed that the retention and fixation of copper reached 0.39 kg⋅m−3 and 85.3%, respectively. Scanning electron microscopy–energy dispersive X-ray spectrometry further disclosed an increasing trend in the composition of CuN from the end inward. X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy analyses later revealed that CuN could be fixed on bamboo in the form of hydrogen bond or complex reaction. Statistical analysis showed that the increasing concentration of CuN from 0.3% to 0.5% and 0.8% (calculated as Cu2+ content) has significant contribution against Trametes versicolor and Gloeophyllum trabeum in comparison with the untreated bamboo. Meanwhile, when the concentration of treating solution increased to 0.8 wt%, the resisting efficacy for Aspergillus niger, Penicillium citrinum and Trichoderma viride soared as high as 85.9%, 94.8% and 70.3%, respectively.